Investigation of bactericidal effect of a mid-infrared free electron laser on Escherichia coli - Toshizo Toyama; Jun Fujioka; Kiyoko Watanabe; Ayaka Yoshida; Takaaki Sakuma; Keitaro Inaba; Takayuki Imai; Takashi Nakajima; Koichi Tsukiyama; Nobushiro Hamada; Fumihiko Yoshino (Scientific Reports, 2022)
Abstract The rapid increase in the number of bacteria that are resistant to many commonly used antimicrobial agents and their global spread have become a major problem worldwide. In particular, for periodontal disease, which is a localized infection, there is a growing need for treatment methods that do not primarily involve antimicrobial agents, and antimicrobial photodynamic therapy (aPDT) is attracting attention. In this study, the bactericidal effects of a mid-infrared free electron laser (MIR-FEL) on E. coli were investigated as a basic study to examine the applicability of MIR-FELs, which can selectively excite molecular vibrations due to their wavelength tunability, to aPDT. The optimal irradiation wavelengths to be examined in this study were determined from the infrared spectrum of the bacteria, which was obtained using Fourier transform infrared spectroscopy. Five irradiation wavelengths (6.62, 6.88, 7.14, 8.09 and 9.26 µm) were selected from the FT-IR spectrum, and we found that the bactericidal effects at a wavelength of 6.62 µm were markedly stronger than those observed at the other wavelengths. At this wavelength corresponding to the Amide II band, the bacterial survival rate decreased significantly as the irradiation time increased. On the contrary, irradiation of a neodymium-doped yttrium aluminum garnet (Nd: YAG) laser at 1.06 µm exhibited no distinct bactericidal effect. No morphological changes were observed after MIR-FEL irradiation, suggesting that a bacterial organelle molecule may be the target of MIR-FEL irradiation, but the exact target was not identified. Furthermore, the temperature change induced in the culture medium by the laser irradiation was ± 1.5 °C at room temperature. These results suggest that the bactericidal effects of MIR-FEL are derived from photochemical reactions involving infrared photons, since E. coli is usually killed by heating it to 75 °C for 1 min or longer.